KINERJA FINANSIAL PERUSAHAAN YANG MELAKUKAN AKUISISI - Elok Sri Utami (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2013)
This study attempts to examine empirical evidence of the firms’ financial performances conducting acquisition at the Indonesian Stock Exchange. A sample of 22 firms undertaking acquisition during 2007-20010 is examined. The t-test for mean difference is employed to examine the performance for the period prior to and after the acquisition. The results show that the firms’ liquidity ratio is not significantly different for the periods before and after acquisition. Total debt to total assets ratio and total debt to equity ratio are significantly different. In particular, the average of these two ratios is higher in the period after the acquisition. This study also documents that the firm activity ratio, measured as total assets turnover, is indifferent between the periods. In addition, the firms’ return on investment and return on equity is lowering after acquisition and the difference is significant. Keywords: acquisition, financial performance,Indonesian Stock Exchange